2018
DOI: 10.3892/ijmm.2018.3884
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epigallocatechin gallate but not chlorogenic acid suppresses EGF-stimulated migration of osteoblasts via attenuation of p38 MAPK activity

Abstract: Phenolic compounds provide health benefits in humans. A previous study by our group has indicated that the epidermal growth factor (EGF)-induced migration of osteoblast-like MC3T3-E1 cells is mediated by the phosphorylation of p44/p42 mitogen-activated protein (MAPK), p38 MAPK, stress-activated protein kinase (SAPK)/c-Jun N-terminal kinase (JNK) and Akt, and that resveratrol, a major polyphenol in grape skin, suppresses the EGF-induced migration by attenuating Akt and SAPK/JNK activation. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In a study involving rats, MSCs treated with PTE revealed that, during initial stages of cell proliferation, the BMP4 mRNA and protein levels were high which confirms the proliferation effect of PTE via upregulation of BMP4 [25]. A higher level of p38 MAPK is associated with enhanced osteoblastogenesis [78]. The MAPK signaling pathway is responsible for altering different mediators like IGF1R, TRAF6, and STE20 which, in turn, affect the bone mineralization and regeneration process [79][80][81].…”
Section: Discussionmentioning
confidence: 82%
“…In a study involving rats, MSCs treated with PTE revealed that, during initial stages of cell proliferation, the BMP4 mRNA and protein levels were high which confirms the proliferation effect of PTE via upregulation of BMP4 [25]. A higher level of p38 MAPK is associated with enhanced osteoblastogenesis [78]. The MAPK signaling pathway is responsible for altering different mediators like IGF1R, TRAF6, and STE20 which, in turn, affect the bone mineralization and regeneration process [79][80][81].…”
Section: Discussionmentioning
confidence: 82%
“…Whilst the suppression of profibrotic pathways including PI3K, STAT3, MMP2, MMP9, PDGF may lead to scar reduction. Phosphorylation of p38 MAPK is inhibited by EGCG [ 65 ]. Catechins inhibit MC-stimulated type I collagen expression by suppressing activation of the PI3k/Akt/mTOR signaling pathways in keloid fibroblasts [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…42 EGF-induced cell migration and EMT through regulating p38-/ERK-MAPK signaling pathway. 40,43,44 EGF activated AMPK by Ca2 +/Calmodulin-dependent kinase under various cellular stresses. 41 The treatment of CRC cell with EGF induced a significant AMPK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%